Social Forestry on a Cost-benefit Analysis Framework - Srivastava, B. P.; Pant, M. M. (Indian Forester, 1979)
Social Forestry is a new concept of forest creation, management, and Judiclous utilization of good and aervices generated therefrom. It aims at combining the idle land, labour and water resources to optimise production of form manure, firewood, fodder, food, small constructional timber, and to atabilise soil. It calls for a monolithic Integration of agriculture. forestry and animal husbandry Social forestry embodies the Gandhian philosophY or self sufficieney, economic grouth and community, development.The concept and potential of social forestry in India has been discused, in this paper. The main constituents of social forestry : farm, rural and urban forestry have been dealt with. The results of seventeen case studies showing their benefit Cost analysis, the employment generated, etc., have been Indicated. These case studies suggest that the total output from the land is a function of the initial investment on tree planting, irrigation and fertilization and that the prodactivity of the man-made forests can be increased by a closer spacing of plants and through irrigation and fertilization. This though entails a higher per unit area investment, is likely to yield higher return a Some pilot project. on social forestry which might have an impact on other States have also been discnussed.For adequate protection and conservation of trees resources mobilized through social forestry, the primary need of defining ownership of trees and sharing benefits have been emphasized. Some criteria for evaluating and allocating funds for social forestry programmes have also been proposed. For the success of social forestry programmes a change in the attitudes of the forester, villager, politician, decision maker and all other. involved is inevitable. Through integrated land u'e planning and extensive social forestry programmes alone, sustained flood control and environmental can be achieved economically.